Guessing the Form of Human Rights in a State of Law - Shivana, Nur - (Lex Scientia Law Review, 2017)
This book on the rule of law and human rights contains material that explains how the rule of law is related to human rights. Of course, the material discussed in this book is closely related to Indonesia because we know that in the 1945 Constitution Article 1 Paragraph 3 reads that "Indonesia is a country based on law". This book explains that the rule of law and human rights cannot be separated, that one of them functions to protect human rights. In a country where human rights law is upheld and protected. Protection in a rule of law against human rights is manifested in the form of normalizing these rights in the constitution and laws and henceforth their enforcement through the judiciary as the executor of judicial power.